2013
DOI: 10.1097/pec.0b013e31829ec0d9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Emergency Medicine Discharge Instructions in Pediatric Head Injury

Abstract: Children sustaining head injury were inadequately instructed to restrict athletic activities upon discharge. This is particularly true for patients who sustain an mTBI from non-sports-related activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Barriers to reporting concussive symptoms such as the desire to 'want to keep playing' have been identified in the literature [36] . Additionally, children who have sustained head injuries have been found to be inadequately instructed to restrict athletic activities upon discharge from emergency departments [37] . Health care providers have an integral role in identifying symptoms and addressing postconcussion symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to reporting concussive symptoms such as the desire to 'want to keep playing' have been identified in the literature [36] . Additionally, children who have sustained head injuries have been found to be inadequately instructed to restrict athletic activities upon discharge from emergency departments [37] . Health care providers have an integral role in identifying symptoms and addressing postconcussion symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…In 5 studies, 50À54 investigators used epidemiologic data, chart reviews, or cross-sectional surveys to identify the recommendations given to those with concussion and adherence to guidelines. Emergency department or trauma center chart reviews 51,54 indicated that children were discharged without adequate concussion-specific activity restrictions (eg, restriction from athletic participation, avoidance of activities that require attention to visual or auditory stimuli). When patients were surveyed, a lack of appropriate return-to-play advice was evident.…”
Section: Compliance With Return To Activitymentioning
confidence: 99%
“…Methods of diagnosis, 4,11 hospital admission criteria, 1,15 identification of child abuse victims, 2,17 and return-to-play criteria 13,14 are just some of the active areas of research. Follow-up care of pediatric patients with minor head trauma, accompanied by surveillance imaging when appropriate, is rendered by primary physicians, neurosurgeons, and sports medicine programs among others.…”
Section: ©Aans 2014mentioning
confidence: 99%